2000
DOI: 10.1136/jnnp.69.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of neurological disorders associated with HIV since the introduction of highly active antiretroviral therapy (HAART)

Abstract: Objective-To determine the change of incidence and prevalence of neurological disorders caused by the human immunodeficiency virus (HIV) and opportunistic infections in HIV positive patients under treatment since the introduction of highly active antiretroviral therapy (HAART). Methods-The data of all HIV infected patients were retrospectively analysed, who were examined in the HIV outpatients clinic of the neurological department of the University Clinic Essen between 1995 and 1998 (n=563, total number of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
168
1
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(182 citation statements)
references
References 15 publications
4
168
1
9
Order By: Relevance
“…This fact has also been observed in the literature [3][4][5][6] . Currently HAART consists of four classes of drugs: nucleoside reverse transcriptase inhibitors and nucleotide analogs (NRTIs) (Lamivudine, Zalcitabine, Zidovudine, Didanosine, Tenofovir, Stavudine and Abacavir); non-nucleoside reverse transcriptase inhibitors (NNRTIs) (Delavirdine, Efavirenz and Nevirapine); protease inhibitors (PIs) (Indinavir, Saquinavir, Ritonavir, Atazanavir and Nelfinavir) and fusion inhibitors 7 .…”
Section: Discussionsupporting
confidence: 72%
“…This fact has also been observed in the literature [3][4][5][6] . Currently HAART consists of four classes of drugs: nucleoside reverse transcriptase inhibitors and nucleotide analogs (NRTIs) (Lamivudine, Zalcitabine, Zidovudine, Didanosine, Tenofovir, Stavudine and Abacavir); non-nucleoside reverse transcriptase inhibitors (NNRTIs) (Delavirdine, Efavirenz and Nevirapine); protease inhibitors (PIs) (Indinavir, Saquinavir, Ritonavir, Atazanavir and Nelfinavir) and fusion inhibitors 7 .…”
Section: Discussionsupporting
confidence: 72%
“…HAART restores immune function, reducing opportunistic infections, and has prolonged the median survival period for patients to 44 months in contrast to 6 months in the pre-HAART era (Dore et al, 2003). The prevalence and incidence of HIV-associated dementia have also decreased since HAART was introduced (Maschke et al, 2000;Sacktor et al, 2001). In a cohort study, patients taking HAART for 3 years showed significant improvement in neurocognitive performance, which was associated with the magnitude of CD4 + cell count increases ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CSF abnormalities in patients with CMV polyradiculopathy can mimic the pattern of acute bacterial meningitis, including a pleocytosis with polymorphonuclear leucocyte preponderance, a raised protein concentration and hypoglycorrhachia or a reduced CSF:plasma glucose ratio 24,25 . Some studies reported 50-76% of patients with CMV poliradiculopathy and "typical" polymorphonuclear preponderant pleocytosis 21 . In our study we confirm a broad spectrum of CSF patterns in CMV polyradiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies performed in developed countries in the HAART era reported a prevalence of CMV encephalitis < 2% 21 . Similar figures have been reported in hospital-based studies in Brazil 28,33 .…”
Section: Discussionmentioning
confidence: 99%